Pigmented/melanocytic malignant perivascular epithelioid cell tumor with TFE3-SFPQ(PSF) rearrangement – a challenging diagnosis of PEComa family of tumors - Anna Szumera-Cieækiewicz; Olga Kuczkiewicz-Siemion; Katarzyna Seliga; Magdalena Grabowska-Kierył; Andrzej Tysarowski; Michał Wągrodzki; Tomasz Świtaj; Monika Prochorec-Sobieszek; Piotr Rutkowski (Polish Journal of Pathology, 2020)
We here report a case of a distinct subtype of pigmented/melanocytic malignant PEComa with TFE3-SFPQ(PSF) rearrangement. The tumor involved the iliac region and clinically mimicked metastatic melanoma. The immunohistochemical assessment was supplemented with molecular studies including fluorescence in situ hybridization (FISH) and next-generation sequencing sarcoma panel (NGS). We also discuss the differential diagnosis of intraabdominal PEComas and emphasise the recent molecular reports on the TFE3 rearranged tumors.